The Effect of Digital Transformational Leadership, Person Organization Fit on innovative Work Behaviour Mediated by Learning Agility and Knowledge Sharing Behaviour at Edutech Company XYZ - Banister, Veronica; Ardi, Ardi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
COVID-19 pandemic has raised awareness of a rapidly changing world marked by uncertainty and rapid changes. This poses a significant challenge for startups, making them vulnerable to organizational sustainability issues due to various factors such as limited funding, a lack of innovation or challenges in human resource management. This phenomenon urges all stakeholders to continuously adapt and strengthen transformative leadership to foster innovation that supports sustainability. Amidst this phenomenon, startup company XYZ has demonstrated ongoing growth and resilience despite the challenges faced by many startups. Therefore, the aim of this research is to measure the influence of digital transformational leadership and person-organization fit on innovative work behavior, mediated by learning agility and knowledge-sharing behavior within company XYZ. The company employs 220 individuals, with 150 of them as respondents to the research questionnaire. Data were processed and analyzed using the PLS-SEM method. The research findings indicate that digital transformational leadership and person-organization fit positively influence innovative work behavior. Additionally, learning agility and knowledge-sharing behavior, as mediating variables between digital transformational leadership and innovative work behavior, have a positive impact. However, knowledge-sharing behavior as a mediation between person-organization fit and innovative work behavior does not have a positive influence.